The influence of halal labels and marketing mix on purchase decisions for Kopi Kenangan online food delivery in Jabodetabek area, Indonesia - Thahira, Hana; Arsyianti, Laily Dwi (Halal Studies and Society, 2025)
Indonesia is increasing its coffee production and consumption rates annually, leading to the proliferation of coffee shops in Jabodetabek and prompting competitors to necessitate online food delivery. Therefore, this research aimed to determine the influence of the halal label and marketing mix comprising product, price, place, and promotion, on online food delivery purchasing decisions for Kopi Kenangan in Jakarta, Bogor, Depok, Tangerang, and Bekasi (Jabodetabek) Area, a metropolitan region including satellite cities and major business centers. The analysis used a quantitative method with purposive sampling, including 151 Muslim respondents aged 13–40 years who had purchased Kopi Kenangan products online. Data were analyzed using Structural Equation Modeling-Partial Least Squares (SEM-PLS). The results showed that product and promotion variables significantly influenced purchasing decisions for Kopi Kenangan products. In contrast, the halal label and location showed a positive but insignificant influence, and price exhibited a negative and insignificant influence.